TINJAUAN LITERATUR SISTEMATIS TENTANG CYBERSECURITY ACCOUNTING: INTEGRASI KEAMANAN SIBER DALAM AKUNTANSI DIGITAL - Sibarani, Grace Fiftyrina; Kesuma, Sambas Ade; Nasution, Fahmi Natigor; Erwin, Keulana (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2025)
This study aims to provide a comprehensive understanding of the evolution of the concept of cybersecurity accounting, its underlying theories, the methodological approaches used in previous research, and identify research gaps for further development. A Systematic Literature Review (SLR) approach was used to analyze 15 Scopus and Elsevier-indexed scientific articles published between 2022 and 2025. The synthesis results indicate that cybersecurity accounting plays a strategic role in ensuring the integrity of financial reports, the reliability of digital audits, and compliance with data security policies. Theories such as Protection Motivation Theory (PMT), Neutralization Theory, and Stewardship Theory serve as the main frameworks in explaining individual behavior and organizational governance towards cyber risks. Meanwhile, the most widely used research method is a survey-based quantitative approach, followed by regression analysis models and empirical exploration. This study identified a research gap in the integration of artificial intelligence (AI) and machine learning (ML) to detect and prevent cyberattacks in accounting systems. Furthermore, cross-national studies and interdisciplinary approaches linking accounting security, ethics, and accountability are still limited. The findings are expected to enrich the literature and form the basis for developing more adaptive accounting security policies in the era of digital transformation.